An Innovation of Children Outdoor Clothing to Increase the Risk of Playground Injuries - Nahrawi, Shuhaila; Mustapha, Shahrizad Fitri; Saidan, Suriati (Idealogy Journal, 2020)
Children need clothes that are suitable to play. Clothing worn not just giving comfort to move, but it will guarantee the safety of the child's body from susceptible to injury. Variety of children's clothing brand now produced according to the needs and comfort of the children. Especially in terms of design, the use of fabrics, clothing accessories capable captivate consumers, such as parents. In the process create a new ideas and design to produce specific clothing for the children play at the playground, various factors and important features should be applied. Appropriateness of clothes according to the age of the child, the use of appropriate materials and fabrics, styles and designs, use of colour and motive is very important. In addition, other factors such as safety, protection and functions of clothing should be preferred. The quality clothing is not just showing the uniqueness of design and comfort, but also has its advantages and importance to the user. eISSN: 2550-214X © 2020. The Authors. Published for Idealogy Journal by UiTM Press. This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives License (http://creativecommons.org/licenses/by-nc-nd/4.0/), which permits non-commercial re-use, distribution, and reproduction in any medium, provided the original work is properly cited, and is not altered, transformed, or built upon in any way.